Visions of Queer Anarchism: Gender, Desire, and Futurity in Omar Ali Khan's Zibahkhana. (June 2019) - Masood, Syeda Momina
Modelled upon American slasher film tropes, Omar Ali Khan's Zibahkhana (2007) is more than a transnational remake. It is a vision of a queer revolution, and imagines queer futures brought about through rural anarchy and violent eroticism. This article reads the masked killer of Zibahkhana as a monstrous queer agency armed with a queer (zombie) militia prepared to consume and transform the heteronormative matrix. Offering an unprecedented and unapologetic representation of queer aggression onscreen, Khan's indie slasher explores queer articulations of desire and anarchy in the figure of the killer, Baby, a queer woman and a murderous cannibal. With Baby, Zibahkhana offers a queer anti-hero, the first of its kind for Pakistani cinema, that challenges normative modes of being, belonging, and desiring. Thus Zibahkhana not only offers a welcome revision of Western slasher film tropes, it blazes a trail for transgressive and incendiary portrayals of queer embodiments and intimacies in Pakistani visual media.